Ideal Convergence of Random Variables - B. Hazarika; S. A. Mohiuddine (Journal of Function Spaces and Applications)
The aim of this paper is to introduce and study the notion of I-convergence of random variables via probabilistic norms. Furthermore, we introduce I-convergence in Lp space and establish some interesting results.